Synthesis of controlled-release calcium peroxide nanoparticles coated with dextran for removal of doxycycline from aqueous system - Amerhaider Nuar, Nurul Nazihah; Md. Jamil, Siti Nurul Ain; Li, Fan; Mat Azmi, Intan Diana; Chiang, Pen Chi; Shean, Thomas Yaw Choong (Multidisciplinary Digital Publishing Institute, 2022)
Nanoscale calcium peroxide (nCP) has turned out to be one of the effective and environmentally friendly approaches for wastewater remediation purposes. The rapid hydrolysis of nCPs and burst oxygen release caused by the high surface-to-volume ratio of nCPs could surpass the appropriate demand for oxygenation and pollutant degradation in the aqueous system. Thus, coated oxidants (COs) have been prepared using polymeric materials to ensure long-term efficacy and slow-release capability. Therefore, the nCPs were first prepared using dextran as a stabilizer to prevent irreversible agglomeration by the chemical precipitation method and had an average mean size of 2.33 ± 0.81 nm. The synthesized nCPs were then coated with dextran to produce dextran-coated nCPs. Their characteristics and effectiveness in doxycycline (DOX) degradation were assessed. The characterization of nCPs and dextran-coated nCPs was performed using X-ray diffractometry (XRD), field emission scanning electron microscopy (FESEM), fourier transform infrared spectroscopy (FTIR), Brunauer, Emmett and Teller analysis (BET), dynamic light scattering (DLS) and thermogravimetric analysis (TGA) techniques. This work suggests that dextran-coated nCPs are beneficial in wastewater treatment practice in terms of the long-term efficacy of DOX degradation potential.